The Effects Of Environmental Uncertainty And Search Costs On Relational Norms In Interfirm Relationships - Park, Minhye; Rhee, Moonki Kyle; Kim, Jungtae (Journal of Applied Business Research, 2017)
Many firms use network perspectives in the context of interfirm relationships, an approach that is causing a rapid change in industrial dynamics. However, although most firms are connected with exchange partners, it is difficult to have positive relationships because of the latter is opportunistic behavior. This study considers the factor of industrial dynamics in interfirm relationships. Thus, we investigate the moderation effect of network embeddedness in relational norms on environmental uncertainty and search costs regarding interfirm relationships. Specifically, we identify network relationships and focus on changes of network norms in a focal firm and its exchange partners. Consequently, this study offers several theoretical and managerial implications, and suggests areas of future research regarding interfirm relationships.